2001
DOI: 10.1021/bp0100880
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Reaction Sets for Escherichia coli Metabolism under Different Growth Requirements and Uptake Environments

Abstract: A computational procedure for identifying the minimal set of metabolic reactions capable of supporting various growth rates on different substrates is introduced and applied to a flux balance model of the Escherichia coli metabolic network. This task is posed mathematically as a generalized network optimization problem. The minimal reaction sets capable of supporting specified growth rates are determined for two different uptake conditions: (i) limiting the uptake of organic material to a single organic compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
124
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 18 publications
0
124
0
Order By: Relevance
“…A range of computational studies have sought to understand phenotypes through determining the essential genes 19,46,51,53,63 , metabolites 44, 60 and reactions 39,47,48,58 in the E. coli metabolic network. A common benchmark for examining GEM predictive ability is to determine the agreement with growth phenotype data from knock-out collections of E. coli.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…A range of computational studies have sought to understand phenotypes through determining the essential genes 19,46,51,53,63 , metabolites 44, 60 and reactions 39,47,48,58 in the E. coli metabolic network. A common benchmark for examining GEM predictive ability is to determine the agreement with growth phenotype data from knock-out collections of E. coli.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…(B) Recent studies utilizing the reconstruction in a prospective manner have aimed to use the current biochemical and genetic information included in the metabolic network along with additional data types to drive biological discovery, such as predicting genes encoding for orphan reactions 32,33,[35][36][37] . (C) Utilizing the reconstruction in phenotypic studies, computational analyses have examined gene 19,46,51,53,63 , metabolite 44,60 and reaction 39,47,48,58 essentiality along with considering thermodynamics 19,40,47,49,52,54,55,57,61 to make better predictions about the physiological state (i.e., the active pathways) of the cell for a given environmental condition. (D) The E. coli reconstructions have been used to analyze and interpret the intrinsic properties of biological networks.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other important work, the iJR904 [45] genome-scale metabolic model of Escherichia coli was applied with mixed-integer linear optimization to predict the minimal set of metabolic reactions needed for E. coli viability in minimal and complex media [46]; the study found that 122 metabolic reactions are required for growth in complex media, with an additional 102 reactions required for growth in minimal media. This is the first work to quantify approximately how many metabolic genes must be added to the minimal organism to obtain growth on defined minimal media instead of undefined complex media (~102 additional genes).…”
Section: Model-driven Design Of a Minimal Metabolismmentioning
confidence: 99%